The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1523/jneurosci.20-18-07059.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Amygdala Modulates Memory Consolidation of Fear-Motivated Inhibitory Avoidance Learning But Not Classical Fear Conditioning

Abstract: Although the lateral and basal nuclei of the amygdala are believed to be essential for the acquisition of Pavlovian fear conditioning, studies using post-training manipulations of the amygdala in the inhibitory avoidance learning paradigm have recently called this view into question. We used the GABA A agonist muscimol to functionally inactivate these nuclei immediately after single-trial Pavlovian fear conditioning or single-trial inhibitory avoidance learning. Immediate post-training infusions of muscimol ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
152
4
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(175 citation statements)
references
References 45 publications
18
152
4
1
Order By: Relevance
“…The results of Experiment 2 also indicate that unilateral intra-BLA infusions of Musc or lidocaine did not affect retention when infused into either the right or left BLA. The lack of effect on retention by Musc and lidocaine is not due to a dosage issue, as previous findings indicate that bilateral intra-amygdala/BLA infusions of the doses used in the current study impair retention (ColemanMesches and McGaugh 1995;Wilensky et al 2000). These findings suggest that the right BLA, but not the left, is involved in the enhancing modulation of memory consolidation induced by intra-BLA infusions and that either BLA alone, intact, and unmanipulated, is sufficient for normal retention.…”
Section: Lateralization Of Memory Enhancement To the Rightblasupporting
confidence: 66%
“…The results of Experiment 2 also indicate that unilateral intra-BLA infusions of Musc or lidocaine did not affect retention when infused into either the right or left BLA. The lack of effect on retention by Musc and lidocaine is not due to a dosage issue, as previous findings indicate that bilateral intra-amygdala/BLA infusions of the doses used in the current study impair retention (ColemanMesches and McGaugh 1995;Wilensky et al 2000). These findings suggest that the right BLA, but not the left, is involved in the enhancing modulation of memory consolidation induced by intra-BLA infusions and that either BLA alone, intact, and unmanipulated, is sufficient for normal retention.…”
Section: Lateralization Of Memory Enhancement To the Rightblasupporting
confidence: 66%
“…Consonant with such view, a number of studies have shown a high density of BDZ sites in the BLA (Niehoff and Kuhar, 1983) and a clear anticonflict effect after the local infusion of BDZ in the BLA (see review by Davis, 1997). Moreover, the pharmacological stimulation of GABA A sites or the stimulation of GABAergic neurotransmission in the BLA induced a robust decrease of fear learning (Wilensky et al, 2000). In fact, inactivation of BLA neurons with a GABA A receptor agonist reduces both the acquisition and expression of fear conditioning (Helmstetter and Bellgowan, 1994;Muller et al, 1997;Wilensky et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…NE agonists infused directly into the amygdala immediately after training enhanced retention (Liang et al 1986(Liang et al , 1990. GABA agonists infused directly into the amygdala immediately after training impaired retention (Castellano et al 1989;Willensky et al 2000). Amygdala is reported to play a crucial role, preferentially in avoidance learning than spatial learning (Takashina et al 1995) and is also involved with the formation of enhanced declarative memory for emotionally arousing events (Adolphs et al 1997;Cahill and McGaugh 1998;Hamann et al 1997).…”
Section: Memory Retention and Cognitionmentioning
confidence: 99%